2017
DOI: 10.1108/tpm-06-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

Top management team diversity and firm performance: exploring a function of age

Abstract: Purpose Based on socioemotional selectivity theory, the authors aimed to develop and test hypotheses that identify the direct effect of top management team (TMT) age diversity on firms’ financial performance (return on equity [ROE], return on assets [ROA]) and the interactive effect of TMT age diversity and TMT average age on firms’ financial performance. Design/methodology/approach The paper presents results from a quantitative study of 867 TMTs in Korean manufacturing firms. Multiple hierarchical regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 64 publications
(114 reference statements)
1
31
0
1
Order By: Relevance
“…Previous research related to the relationship between TMT age diversity and performance have been globally and locally (in Indonesia) conducted; however, the results have not been consistent (Kilduff et al , 2000; Webber and Donahue, 2001; Ozer, 2010; Nielsen and Nielsen, 2013; Talavera et al , 2017; Tanikawa et al , 2017; Rompis et al , 2018). Some studies have found a positive relationship (Kilduff et al , 2000), while others have identified negative (Ozer, 2010; Talavera et al , 2017; Tanikawa et al , 2017) and non-significant relationships (Webber and Donahue, 2001; Nielsen and Nielsen, 2013; Rompis et al , 2018). Furthermore, various results have shown that diversity in directors is like a double-edged sword, as the theory stated by Williams and O’Reilly (1998), which had positive and negative impacts.…”
Section: Introductionmentioning
confidence: 92%
“…Previous research related to the relationship between TMT age diversity and performance have been globally and locally (in Indonesia) conducted; however, the results have not been consistent (Kilduff et al , 2000; Webber and Donahue, 2001; Ozer, 2010; Nielsen and Nielsen, 2013; Talavera et al , 2017; Tanikawa et al , 2017; Rompis et al , 2018). Some studies have found a positive relationship (Kilduff et al , 2000), while others have identified negative (Ozer, 2010; Talavera et al , 2017; Tanikawa et al , 2017) and non-significant relationships (Webber and Donahue, 2001; Nielsen and Nielsen, 2013; Rompis et al , 2018). Furthermore, various results have shown that diversity in directors is like a double-edged sword, as the theory stated by Williams and O’Reilly (1998), which had positive and negative impacts.…”
Section: Introductionmentioning
confidence: 92%
“…Age is commonly explained as the length of time for which an individual has been alive. Manager's age is usually discussed in terms of younger and older dimensions [33]. The age of managers affects their perceptions, beliefs and decision-making styles.…”
Section: Manager's Age and Sustainable Corporate Performancementioning
confidence: 99%
“…Age has been argued by literature to be negatively associated with risk preference, and positively with organisational inertia and status quo (Hambrick & Mason 1984). As age implies maturity (Tanikawa, Kim & Jung 2017), older directors possess more ability to predict benefits and risks of strategic decisions. However, more recent previous literature find inconclusive evidence on the relationship between age and several aspects of firm performance, for example, acquisition performance (Field & Mkrtchyan 2016) and corporate social responsibility performance (Harjoto, Laksmana & Lee 2015).…”
Section: Tax Planning Its Components and Top Management Team Characteristicsmentioning
confidence: 99%